2007
DOI: 10.1002/app.27381
|View full text |Cite
|
Sign up to set email alerts
|

Microgel formation and thermo‐mechanical properties of UV‐curing unsaturated polyester acrylates

Abstract: The effect of internal and terminal unsaturation on the properties of the acrylated polyester films was investigated. Four types of acrylated polyester resin were prepared using adipic acid, maleic anhydride, neopentyl glycol, trimethylolpropane, and acrylic acid. Terminal and internal double bond content as well as branching was adjusted by the molar quantities of trimethylolpropane and maleic anhydride, respectively. A reactive diluent, trimethylolpropane triacrylate (TMPTA), was also used. A three-factor, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The morphology was heterogeneous, composed by a phase rich in crosslinked UP (UP rich ) embedded in a less crosslinked phase rich in PS (ST rich ) 34 . The UP rich domains can be assigned to microgels generated by nanophase separation during the curing reaction 25,35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology was heterogeneous, composed by a phase rich in crosslinked UP (UP rich ) embedded in a less crosslinked phase rich in PS (ST rich ) 34 . The UP rich domains can be assigned to microgels generated by nanophase separation during the curing reaction 25,35 …”
Section: Resultsmentioning
confidence: 99%
“…It was calculated using Equation ρ=E'3italicRT, where R is the universal gas constant, E' is equilibrium storage modulus in the rubber zone achieved using dynamic‐mechanical analysis (DMA) measurements, and T is the absolute temperature in the rubber zone calculated as TnormalgUPrich + 40°C in order to ensure the plateau zone 16,25 …”
Section: Methodsmentioning
confidence: 99%
“…The breadth of the α-relaxation is closely related to the heterogeneity of a polymer network . Previous studies have shown that polyfunctional crosslinkers and highly branched systems tend to afford more heterogeneous networks due to the formation of microgels and phase separation. These densely crosslinked regions are undesirable because they can act as defect sites that negatively impact the mechanical properties of the film. Here, no significant changes were observed in the height or the breadth of the α-relaxation, suggesting that homogeneous crosslinked networks were obtained, regardless of the extent of branching.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent work, the authors [46] used the same type of UPs to obtain UV-cured films and studied how the extent of microgelation affected the viscoelastic, fracture and tensile properties of the films. The results demonstrated that when the microgelation occurred in a low extent, the microgels acted as micro-support units enhancing the mechanical properties.…”
Section: Ways To Tailor and Improve The Properties Of The Ups And Uprsmentioning
confidence: 99%